Ways of Concealment for Iatrogenic Crimes, Traces of Their Commission and Forensic Methods of Their Identification - M. V. Tuzlukova (Теория и практика судебной экспертизы, 2020)
The article discusses specific features of the ways of concealing iatrogenic crimes and traces indicating them. Concealment of information, destruction of crime traces, falsification of medical records, staging and mixed methods of concealment form a system of ways to cover up such crimes. It is noted that there is a direct correlation between the methods of concealment of iatrogenic crimes and the severity of the consequences for the patient. The greater the harm done to the victim, the more sophisticated the concealment methods are used to evade criminal liability. The need is recognized to create specific research methodologies for the destroyed traces and ways and tools of destruction of physical sources of information as well as the methodologies for forensic handwriting and technical examination of the falsified medical documents, forensic computer analysis of the altered digital data related to the event under investigation.The evidence of the ways of the iatrogenic crimes’ and their traces’ cover-up are used when initiating leads and planning the investigation, choosing the techniques of interrogation, search, examination and some other investigatory actions. The solution and effective investigation of iatrogenic crimes require knowledge of the existing ways of concealing them, as well as of the methods of their detection and exposure.